Service Quality Analysis to Increase Customer Satisfaction Coffee Shop - Klementius, David; Nurtanto, Maynard Blenda; Muhammadiah, Rizqi Fatha; Prasetyo, Rizky Muhamad (Journal of Current Research In Multidisciplinary, 2023)
This research aims to find out how good service quality cafe is for consumers. This study uses data collection techniques in the form of questionnaires through the Google Forms platform. The population in this study were all cafe customers on campus. In this study, the samples taken included 30 respondents. In taking the sample, the method used is purposive sampling. The results of the IPA analysis show that cafes are still lacking in providing services to their customers. Apart from that, based on the data that the author obtained, the number of consumers who have made transactions said that the level of interest in cafe services is still low, so this makes consumers less interested in coming and buying. Then cafes still have to improve the quality of their service to consumers.